The Ethical and Principled Leadership Crisis on a Strategic Level: Experiencing by South African Police Service - (:unkn) unknown (My University, 2025)
Leadership is the root of all organisational issues, and its social position is institutionalised and recognised. Police professionalism and sustaining police integrity are two things that are frequently cited as being most dependent on police leadership. Law enforcement officers must be moral role models. Whether there is accountable leadership or not, it will ultimately have a big impact on society. This research responds to a call for further research on leadership in the South African Police Service. Effective police leaders become adept at responding to challenges. Ethical leadership is a necessary ingredient for successful crisis management. This study aims to critically analyse the ethical leadership crisis within the SAPS, to identify its contributing factors, and to explore potential strategies for promoting ethical and principled leadership within the organisation. Police leaders are responsible for preserving democratic, economic and professional values in their capacity as leaders, in both the short and long term. They should be able to master and deal with daily operations, emergency events and various types of crises, incremental developments and reforms, both separately and simultaneously. This comprises a large range of situations and management tasks. Against this background, it will be argued that leadership both within and by the police has become more complex and challenging in recent years. At the same time, it is believed that police leadership is a crucial resource in order to ensure the efficient operation and development of the police service, and is essential if the police are to function efficiently with the level of quality and ethical standards that meet the demands and expectations of a liberal democracy. Drawing a direct line between these two may be oversimplified, but there is unquestionably a connection between the leadership issues that have plagued the SAPS for many years and the agency's declining effectiveness in p
Keywords: African Research